Audit into reasons for maternal request for caesarean sections at the Norfolk & Norwich University Hospital NHS Foundation Trust. (16th November 2010) - Bircher, C; Toeima, E; Hamouda, T; Warren, R
Abstract : Objectives: To determine (1) percentage of Caesarean section (CS) for maternal request in our unit; (2) reason for request; (3) how can the authors reduce the number of requests. Methods: 227 patients identified from electronic database. 177 considered as 'maternal request' LSCS (lower segment Caesarean section) for various reasons, that is, 26.1% of all LSCS. Patients were divided into groups: Group 1: Simple maternal request: seven cases (of 177 = 4.0%). Group 2: Minor medical reason (but not medically advised): 16 cases (out of 177=9.0%). Group 3: One previous C/S: 74 cases (out of 177=41.8%). Group 4: One previous C/S+other medical problem: 16 cases (out of 177=9.0%). Group 5: Breech, ECV (external cephalic version) not offered/declined: 41 cases (out of 177=23.1%). Group 6: Twins, first baby cephalic: 23 cases (out of 177=13.0%). Results: Very low documented evidence of discussion regarding future family/fertility (12.4%) and regarding risks of CS (38.9%). There is a need to improve counselling skills. 51% of the CS was done after one previous LSCS. 23% of 'maternal request' LSCS done for breech with no ECV. The authors need to improve our ECV services. Conclusion: Setting a specialised vaginal birth after Caesarean (VBAC) clinic could be helpful. After emergency Caesarean section, it is important to review the patient and discuss the events of labour. Discussion about options for mode of delivery in future pregnancies needs to be clearly documented, as well as encouragement to have VBAC unless contraindicated.